The Philosophy of Ethics in Ibn Sina (Comprehensive Journal of Science, 2026)
This research explores the integrative approach in Ibn Sina's philosophy of ethics, highlighting how he formulated ethics as a rigorous science linking physical health with spiritual rectitude. The study begins with Ibn Sina's methodology in "psychological philosophy," focusing on the role of the appetitive and irascible faculties, culminating in the state of "justice," which he considers divine recognition. The research also clearly examines the close connection between "satisfaction" and ethics, considering the virtue of the "golden mean" as vital to existence. Furthermore, the study sheds light on Ibn Sina's reconciliation of Greek wisdom and Islamic law, where the Prophet represents the perfect model of both law and ethics. The research concludes that the ultimate goal of ethics is "supreme happiness" and connection with the ideal world, thus transforming ethics from an individualistic control into a stable foundation for the ideal society.
Keywords: Golden Mean - Supreme Happiness